2021
DOI: 10.1016/j.psj.2021.101308
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative role of trans-ferulic acid on induced oxidative toxicity of rooster semen by β-cyfluthrin during low temperature liquid storage

Abstract: Current study was designed to evaluate the effects of β-cyfluthrin, as a toxicant substance, and trans -ferulic acid ( trans - FA ), as a protective agent, on different parameters of rooster semen upon liquid storage. For this purpose, semen samples of roosters (Ross 308, n = 10, 32-wk-old) were collected twice a week. Good quality samples (≥70% progressive motion) were diluted, pooled and then divided for the purposes of the study. In the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
(57 reference statements)
0
17
1
Order By: Relevance
“…Moreover, due to the high lipophilicity of β -cyfluthrin, it could easily penetrate via cell membranes and exert its detrimental effects within the cells [ 39 ]. Previous reports revealed that peroxidative reaction is one of the pathways of induced toxicity by pyrethroid insecticides over in vitro exposure [ 10 , 40 , 41 ]. According to the results of MTT (in the first and second experiments) and MDA levels, the current study confirmed that β -cyfluthrin induces oxidative toxicity in the primary culture of rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, due to the high lipophilicity of β -cyfluthrin, it could easily penetrate via cell membranes and exert its detrimental effects within the cells [ 39 ]. Previous reports revealed that peroxidative reaction is one of the pathways of induced toxicity by pyrethroid insecticides over in vitro exposure [ 10 , 40 , 41 ]. According to the results of MTT (in the first and second experiments) and MDA levels, the current study confirmed that β -cyfluthrin induces oxidative toxicity in the primary culture of rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, degenerative changes and reduced hepatocyte viability were indicated after exposure to cypermethrin or pyrrolidine alkaloids [ 46 , 47 ]. The reduction of hepatocyte viability in the group treated with β -cyfluthrin (alone) might be strongly related to the generation of free radicals, stimulation of peroxidative and nitrosative reactions, a significant increase in MDA and TNN levels, and ultimately reduction of enzymatic antioxidant amount [ 10 , 48 ]. Moreover, the results of the current study revealed the hepatoprotective role of luteolin against toxic doses of β -cyfluthrin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations